تطبيقات التمويل بالمرابحة فى القطاع المصرفى السودانى ومشكلاتها ( 2000 - 2012 م ) - الطيب، عبدالمنعم محمد (أكاديمية السودان للعلوم المصرفية والمالية - مركز البحوث والنشر والاستشارات, 2014)
The research is entitled Murabaha Financing application in Sudanese banking Sector and it is problems (2000-2012). The Sudanese banks intent to apply Islamic modes of finance instead of the interest rate finance adopted in conventional banking. Islamic banks in Sudan began to applying different modes of finance such as Musharaka, Mudharaba, Salam, and Murabaha until the total number of modes reached 14. However, Murabaha is the most applied mode. The majority of the Islamic banks concentrated on this mode and preferred it to other modes. Consequently, the research examines the application of Murabaha in Sudanese Banks. The research attempts to answer these questions: what is the level of commitment of Islamic Banks with Central Bank regulations regarding Murabaha finance? What is the share of this mode of finance compared to other modes? Do profit margins specified by the Central Bank exceed the actual inflation rate? What is the nature of the challenges facing Murabaha application for banks and clients from demand and supply sides? The research adopts historical, analytical and case study methodologies to answer the questions. The research arrives at the following results: Murabaha is the most widely used mode of finance in Sudanese Banking system compared to other modes. Ratios of finance in this mode deviated negatively from the ratios prescribed by the Central Bank. Moreover, actual inflation rates in some years were higher than profit margins prescribed by the Central Bank. Furthermore , There is a lack of training for all parties involved in applying Murabaha and other modes. The research recommends encouraging application of other modes of Islamic finance, reconciling between the central bank and the commercial banks with respect to specification of Murabaha regulation, spreading the culture of banking practice, and preparing scientific directories associated with legal and banking aspects. These directories need to updated by bankers and legal advisors. Furthermore, the research recommends activation of the role of the legal supervisory institutions in relation to legal contract provisions as well as more attention for training and qualification for banks’ employees for the purpose of getting to know the proper application techniques of Islamic modes of financing including Murabaha.
يأتي هذا البحث بعنوان: تطبيقات التمويل بالمرابحة في القطاع المصرفي السوداني ومشكلاتها (2000 -2012م)، قامت المصارف بتطبيق صيغ التمويل الإسلامي. بدلا عن التعامل بأسعار الفائدة الذي تستخدمه المصارف التقليدية أخذا وعطاءا، وقد بدأت المصارف الإسلامية باستخدام صيغ محددة كالمشاركة والمضاربة والسلم والمرابحة حتى وصل إجمالي الصيغ المستخدمة إلى أربعة عشرة صيغة، إلا أن الصيغة الأكثر تطبيقا كانت المرابحة، ولقد ركزت عليها معظم المصارف وتم تفضيلها عن باقي الصيغ الأخرى، لذا يحاول البحث دراسة تطبيق هذه الصيغة في المصارف السودانية. يحاول البحث الإجابة على بعض الأسئلة تمثلت في الاتي؛ ما مدى التزام المصارف السودانية بالضوابط المحددة من قبل البنك المركزي للتمويل بالمرابحة؟ وما هي الأهمية النسبية للتمويل بالمرابحة مقارنة بصيغ التمويل الأخرى؟ وهل تجاوزت هوامش الأرباح المحددة من قبل بنك السودان المركزي معدلات التضخم الحقيقية؟ وما هي طبيعة المشكلات التي تواجه تطبيق المرابحة بالنسبة للمصارف والمتعاملين في جانبي العرض والطلب؟ وقد اعتمد البحث على المنهج التاريخي والتحليلي. توصل البحث إلى عدة نتائج تمثلت في أن المرابحة كانت الصيغة الأكثر استخداما لدى المصارف السودانية مقارنة بصيغ التمويل الأخرى، كما شكلت نسبة التمويل بها انحرافا سلبيا عن النسب المقررة بواسطة بنك السودان المركزي، كما أن معدلات التضخم الحقيقية في بعض السنوات قد تجاوزت نسبة هوامش الأرباح المرسومة المحددة، هذا بالإضافة إلى أن التمويل بالمرابحة وصيغ التمويل الأخرى تواجه نقصا في التدريب لكل الأطراف ذات الصلة. أوصى البحث بضرورة السعي نحو تشجيع استخدام صيغ التمويل الأخرى، والتوفيق بين البنك المركزي والمصارف بشأن تحديد ضوابط المرابحة، مع الاهتمام بنشر ثقافة العمل المصرفي وإعداد المراشد العملية المرتبطة بالجوانب الشرعية والمصرفية مع تحديثها من قبل الخبراء المصرفيين والشرعيين، وكذلك تفعيل دور هيئات الرقابة الشرعية في إحكام العقود الشرعية مع الاهتمام بالتدريب والتأهيل اللازمين للعاملين بالمصارف بغرض الإلمام بتقنيات التطبيق السليم لصيغ التمويل الإسلامي بما فيها المرابحة.
Keywords: التمويل المصرفى -- التمويل بالمرابحة -- المصارف السودانية -- بنك السودان المركزى -- الاقتصاد السودانى